Early childhood education and care practitioners’ beliefs and perceptions about preschool children’s risky play - Yokum, Chelsie (Kansas State University, 2018)
Risk and challenge in children’s play have steadily declined over the last 30 years due to adult fears about injuries and litigation, among other factors. This societal trend is important to remedy because not only do children miss out on the numerous crucial benefits in every domain that play, and specifically risk and challenge in play, provides, but research suggests it also can lead to a host of other problems like childhood obesity, more injuries as children create their own risk and challenge in inappropriate ways, and childhood psychopathology. Data on children in care demonstrate a large number of children enrolled in pre-kindergarten programs today, therefore it is important to understand young children’s risky play in the education context and the role that early childhood practitioners play in either supporting or hindering that play. The present study used an original survey derived from the literature to examine early childhood practitioners’ beliefs and perceptions about preschool children’s risky play, practitioner’s risky play practices, and the factors that influence those beliefs and practices. The results showed that practitioners generally had more positive than negative beliefs about risky play, but only rarely or occasionally allowed risky play to occur in their classrooms or centers. A variety of both global and situational factors influenced practitioners’ decisions to allow risky play or not. Participants’ beliefs and practices were positively correlated, and beliefs and practices were both negatively correlated with influences. Numbers of years of experience in the field and education level were not found to be significant predictors of participants’ risky play beliefs and practices. These results have implications for professional development trainings as well as teacher education programs.
Keywords: risky play; preschool; play; teacher beliefs; rough-and-tumble play